Public Organizations and Their Role in Preserving Ethnic Identity (on the Example of the Korean Diaspora) (Journal of Oriental Studies, 2019)
One of the distinguishing features of the existence of a diaspora is the formation of associations and organizations whose activities are aimed at preserving cultural values. The Korean diaspora around the world has similar organizations. In the post-Soviet countries, there are associations of Koreans. The object of the research is the Koreans of Kazakhstan, and its subject is the ethnic identity of the Koreans of Kazakhstan in the context of the growing importance of social ethnic organizations. The content-analysis of modern academic literature and analytical and statistical materials from the archive of the Association of Koreans in Kazakhstan has become a methodological approach to the work. The hypothesis of this study is that the preservation of the ethnic identity of the modern Korean diaspora in Kazakhstan, which is based on representatives of the third and fourth generation, is one of the results of the activities of public organizations on the example of the Association of Koreans in Kazakhstan. Favorable conditions for the revival of ethnic identity have become a devotee to the emergence of ethnic organizations of an ethnic type. The main activity of such organizations is aimed at consolidating the representatives of one ethnos and preserving the original culture. All these factors form a certain role of public organizations in the preservation of ethnic identity. Key words: public organizations, Association of Koreans of Kazakhstan, ethnic culture, ethnic identity.